Uporaba nevronavigacijskega sistema na Oddelku za nevrokirurgijo Splošne bolnišnice Maribor - Ravnik, Janez (Zdravniški vestnik, 2004)
Background. Neuronavigational system is a computerised system for intraoperative planning and guidance of neurosurgical procedures using interactive image presentation. The application of such system is denoted as neuronavigation. There are many neuronavigational systems with different technical solutions for intraoperative guidance. Methods. From June 2002 till April 2003 fourteen patients (mean age 52 years) were operated using of neuronavigational system on department of neurosurgery in Maribor General Hospital. We used neuronavigational system based on infrared light detection and intraoperative guidance with the help CT imaging in three-planes. Results. The system was used in four cases of biopsy, four cases of lesion reduction and six cases of total lesion removal. 11 brain lesion were situated subcorticaly or deeper, two were cortical and one was osteolitic lesion of the skull bone. Lesions mean diameter was 3.5 cm. Calculated accuracy of interactive image-guidance was good in all 14 cases. Conclusions. Neuronavigational system which we used is simple and quite accurate. Its usage improves speed, safety and accuracy of most neurosurgical procedures.
Keywords: Brain neoplasms; kirurško zdravljenje; medicinski instrumenti; možgani; Možgani, novotvorbe; neurology; Neuronavigation; Neurosurgery; Nevrokirurgija; nevrologija; Nevronavigacija